Web development with jQuery - York, Richard (Indianapolis, IN : Wrox, a Wiley brand, 2015)
Newly revised and updated resource on jQuery's many features and advantages Web Development with jQuery offers a major update to the popular Beginning JavaScript and CSS Development with jQuery from 2009. More than half of the content is new or updated, and reflects recent innovations with regard to mobile applications, jQuery mobile, and the spectrum of associated plugins. Readers can expect thorough revisions with expanded coverage of events, CSS, AJAX, animation, and drag and drop. New chapters bring developers up to date on popular features like jQuery UI, navigation, tables, interacti.
Part I: The jQuery API. Introduction to jQuery -- Selecting and Filtering -- Events -- Manipulating Content and Attributes -- Iteration of Arrays and Objects -- CSS -- AJAX -- Animation and Easing Effects -- Plugins -- Scrollbars -- HTML5 Drag and Drop -- Part II: jQuery UI. Draggable and Droppable -- Sortable -- Selectable -- Accordion -- Datepicker -- Dialog -- Tabs -- Part III: Popular Third-Party jQuery Plugins. Tablesorter -- Creating an Interactive Slideshow -- Working with HTML5 Audio and Video -- Creating a Simple WYSIWYG Editor -- Part IV: Appendices. Appendix A: Exercise Answers -- Appendix B: jQuery Selectors -- Appendix C: Selecting, Traversing, and Filtering -- Appendix D: Events -- Appendix E: Manipulating Content, Attributes, and Custom Data -- Appendix F: More Content Manipulation -- Appendix G: AJAX Methods -- Appendix H: CSS -- Appendix I: Utilities -- Appendix J: Draggable and Droppable -- Appendix K: Sortable -- Appendix L: Selectable -- Appendix M: Animation and Easing Effects -- Appendix N: Accordion -- Appendix O: Datepicker -- Appendix P: Dialog -- Appendix Q: Tabs -- Appendix R: Resizable -- Appendix S: Slider -- Appendix T: Tablesorter -- Appendix U: MediaElement.
Includes index.
Vendor-supplied metadata.
Keywords: JavaScript (Computer program language); Query languages (Computer science); JavaScript (Computer program language); Open source software; Query languages (Computer science); Web site development; COMPUTERS -- Programming Languages -- JavaScript; JavaScript (Computer program language); Query languages (Computer science); Electronic books